The Library Settlement Partnerships: A Case Study - MacDonald, Susan L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This in-progress doctoral dissertation research is a qualitative exploratory case study of the Library Settlement Partnerships, a federal government program that consists of partnerships among service providing organizations and public libraries in Ontario. The study explores the ways that service provision in cross-sectoral collaborations is being negotiated among the various stakeholders. Cette étude doctorale en cours repose sur une étude de cas qualitative et exploratoire du Partenariat d'établissement par l'intermédiaire des bibliothèques, un programme fédéral constitué d'un partenariat entre les fournisseurs de services et les bibliothèques publiques de l'Ontario. Cette étude explore comment les différents intervenants offrent leurs services dans le cadre d'une collaboration intersectorielle.